PARTISIPASI MASYARAKAT DALAM PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI DESA NAUMBAI KECAMATAN KAMPAR KABUPATEN KAMPAR - Marulis Marulis; Tri Sukirno Putro; Yusni Maulida (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
This study aims to analyze Community Participation in Community-Based DrinkingWater and Sanitation Provision Programs (Pamsimas) in Naumbai Village, KamparDistrict, Kampar Regency. A sample of 41 people consisting of 3 village officials, 5community leaders and 33 ordinary people. Measurements were made using aquestionnaire in the form of a Likert Scale, while the technique of analyzingcommunity participation was to use the average method. The results of the studyfound that community participation in the community-based drinking water andsanitation (PAMSIMAS) program in Naumbai Village, Kampar District, KamparDistrict had participated well, this was evident from the involvement of villagecommunities in PAMSIMAS activities.